Remote Work, Employee Mix, and Performance - Cevat Giray Aksoy; Nicholas Bloom; Steven J. Davis; Victoria Marino; Cem Özgüzel (Institute of Labor Economics (IZA), 2025)
We study the shift to fully remote work at a large call center in Turkey, highlighting three findings. First, fully remote work increased the share of women, including married women, rural and smaller-town residents. By accessing groups with traditionally lower labor-force participation the firm was able to increase its share of graduate employees by 14% without raising wages. Second, workforce productivity rose by 10%, reflecting shorter call durations for remote employees. This was facilitated by a quieter home working environment, avoiding the background noise in the office. Third, fully remote employees with initial in-person training saw the higher long-run remote productivity and lower attrition rates. This underscores the advantages of initial in-person onboarding for fully remote employees.
Keywords: J2; J3; R1; 330; productivity; workforce mix; remote jobs; work from home